Tetraspanin 3: A central endocytic membrane component regulating the expression of ADAM10, presenilin and the amyloid precursor protein - Seipold, Lisa; Damme, Markus; Prox, Johannes; Rabe, Björn; Kasparek, Petr; Sedlacek, Radislav; Altmeppen, Hermann; Willem, Michael; Boland, Barry; Glatzel, Markus; Saftig, Paul (Biochimica et biophysica acta. Molecular cell research, 2017)
Despite existing knowledge about the role of the A Disintegrin and Metalloproteinase 10 (ADAM10) as the α-secretase involved in the non-amyloidogenic processing of the amyloid precursor protein (APP) and Notch signalling we have only limited information about its regulation. In this study, we have identified ADAM10 interactors using a split ubiquitin yeast two hybrid approach. Tetraspanin 3 (Tspan3), which is highly expressed in the murine brain and elevated in brains of Alzheimer´s disease (AD) patients, was identified and confirmed to bind ADAM10 by co-immunoprecipitation experiments in mammalian cells in complex with APP and the γ-secretase protease presenilin. Tspan3 expression increased the cell surface levels of its interacting partners and was mainly localized in early and late endosomes. In contrast to the previously described ADAM10-binding tetraspanins, Tspan3 did not affect the endoplasmic reticulum to plasma membrane transport of ADAM10. Heterologous Tspan3 expression significantly increased the appearance of carboxy-terminal cleavage products of ADAM10 and APP, whereas N-cadherin ectodomain shedding appeared unaffected. Inhibiting the endocytosis of Tspan3 by mutating a critical cytoplasmic tyrosine-based internalization motif led to increased surface expression of APP and ADAM10. After its downregulation in neuroblastoma cells and in brains of Tspan3-deficient mice, ADAM10 and APP levels appeared unaltered possibly due to a compensatory increase in the expression of Tspans 5 and 7, respectively. In conclusion, our data suggest that Tspan3 acts in concert with other tetraspanins as a stabilizing factor of active ADAM10, APP and the γ-secretase complex at the plasma membrane and within the endocytic pathway.
Keywords: receptory Notch; mozek - chemie; Protein Transport; techniky dvojhybridového systému; neurony; Brain Chemistry; Two-Hybrid System Techniques; Presenilin; proteiny nervové tkáně; protein ADAM10; tetraspaniny; Animals; Nerve Tissue Proteins; Receptors, Notch; kadheriny; vazba proteinů; ADAM10; Neurons; Humans; Mice; Amyloid Precursor Protein Secretases; Tetraspanins; APP; buněčná membrána; Gene Expression Regulation; Cadherins; Tetraspanin; Presenilins; endozomy; Membrane Proteins; regulace genové exprese; Amyloid beta-Protein Precursor; Protein Binding; Cell Line, Tumor; ADAM10 Protein; mozek; nádorové buněčné linie; zvířata; membránové proteiny; Endosomes; Endocytosis; amyloidový prekurzorový protein beta; transport proteinů; Cell Membrane; HEK293 Cells; Brain; endocytóza; lidé; HEK293 buňky; Signal Transduction; preseniliny; signální transdukce; myši; sekretasy